Development of a Social Guidance Program Based on Erik Erikson’s Theory to Foster an Edupreneurial Spirit in Early Adulthood - Riska Nur Asri; Mudafiatun Isriyah; Dewi Masyitoh (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to develop a social guidance program based on Erik Erikson’s psychosocial development theory, specifically at the Intimacy vs. Isolation stage, to foster an edupreneurial spirit among individuals in early adulthood (ages 19–30). The research addresses challenges faced by young adults, including limited capacity to form meaningful social relationships, low collaboration levels, and minimal interest in social entrepreneurship—factors that hinder optimal personal growth in educational and social contexts. The primary objective is to produce a guidance program that empowers young adults to build healthy, productive relationships while instilling edupreneurial values such as collaboration, social initiative, and network-based learning. Employing a Research and Development (R&D) methodology, the study follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection involved observations, interviews, and validation questionnaires, analyzed through thematic qualitative techniques and quantitative methods including descriptive statistics and difference testing. The resulting program is expected to be both feasible and effective, suitable for implementation in higher education institutions and youth communities. It contributes to the cultivation of entrepreneurial character grounded in social values and interpersonal development. The findings highlight the importance of integrating psychosocial theory into educational interventions to support youth empowerment and sustainable social innovation. Furthermore, the program offers practical implications for educators, counselors, and youth facilitators seeking to enhance relational competencies and entrepreneurial mindset among young adults in diverse social settings.